Perancangan Data Mart Analisis Data Nilai Siswa pada SMAN 2 Tebo - Melladia, Melladia; Indah Febri Annisa; Surya Kharisma Karnefo (Yayasan Literasi Sains Indonesia, 2024)
Data Mart is designed to analyze, extract and turn data into information so that it can obtain hidden knowledge and patterns from the processing of available datacollected by researchers on student value data at SMA Negeri 2 Tebo which is difficult to solve using ordinary analysis techniques. With Data Mart, it can provide convenience in analysis which provides advice for schools, focused on top-level management administration in deciding on business decisions. Data Mart is also designed using the Data Warehousing Analysis Process strategy method which includes business drivers, business objectives, high level business information analysis, roles and processes, key performance indicators, dimensions and events and sources and transformation. Data Mart is designed to process the grades of school students at SMA Negeri 2 Tebo. By using a data mart to process student score data to be more effective and efficient and gain knowledge that is useful in making decisions to make future strategies and shorten the time in analysis, you will get the right result.